Rancang Bangun Sistem Informasi Media Pembelajaran Interaktif Bahasa Inggris Berbasis Web - Topan Setiawan; Anggit Suryopratomo; M. Fandra Yudha; M. Imam Maulana (Jurnal Accounting Information System (AIMS), 2022)
English is an international language that has been used almost all over the world with the number of speakers increasing every year. According to The Ethnologue, currently the number of English speakers has reached 1.45 billion people. With these facts, English is a language that should be mastered by everyone in the current era. However, there are still many people who find it difficult for various reasons. By utilizing the development of information systems and information technology in the modern era, the author intends to design an interactive web-based English learning media information system, where the system design method used is Kanban with Unified Modeling Language (UML) modeling tools. The programming language used is PHP, Laravel framework, and MySQL database. From the design results obtained an interactive learning software equipped with pictures, audio, video, animation, and exercise, so that it is hoped that it will be able to improve students' English skills.